Dual in vivo T cell depleted haploidentical hematopoietic stem cell transplantation with post-transplant cyclophosphamide and anti-thymocyte globulin as a third salvage transplant for leukocyte adhesion deficiency with graft failure: a case report - Kiumarsi, Azadeh; Alaei, Amirarsalan; Nikbakht, Mohsen; Mohammadi, Saeed; Ostad-Ali, Mohammad Reza; Rasti, Zahra; Rostami, Tahereh (Frontiers in Immunology, 2025)
BackgroundWith recent advances in clinical practice, including the use of reduced-toxicity conditioning regimens and innovative approaches such as ex vivo TCRαβ/CD19 depletion of haploidentical donor stem cells or post-transplant cyclophosphamide (PTCY), hematopoietic stem cell transplantation (HSCT) has emerged as a curative treatment option for a growing population of patients with inborn errors of immunity (IEI). However, despite these promising developments, graft failure (GF) remains a significant concern associated with HSCT in these patients. Although a second HSCT is the only established salvage therapy for patients who experience GF, there are no uniform, standardized strategies for performing these second transplants. Furthermore, even less data is available regarding the outcomes and best practices for a third HSCT as a salvage measure when a second HSCT fails to achieve engraftment.Case presentationA 6-year-old boy with leukocyte adhesion deficiency type I (LAD-I) experienced GF after the first and second HSCT from a matched unrelated donor. As a salvage measure, the patient received a dual in vivo T-cell depleted haploidentical HSCT. The conditioning regimen for this third HSCT included anti-thymocyte globulin (ATG) and PTCY. Complete donor chimerism was assessed using the short tandem repeat (STR) PCR technique. By day +28 after the transplant, the expression of the leukocyte adhesion molecules CD18, CD11b, and CD11c on the patient’s peripheral blood neutrophils had recovered to over 99%. It remained stable throughout the 18-month follow-up period.ConclusionT-cell replete haploidentical HSCT with ATG and PTCY may be a viable salvage option for LAD patients who have rejected prior HSCT.